Impact of a smoking cessation educational program on nurses' interventions - Sarna, Linda P; Bialous, Stella Aguinaga; Kraliková, Eva; Kmetova, Alexandra; Felbrová, Vladislava; Kulovaná, Stanislava; Malá, Katerina; Roubicková, Eva; Wells, Marjorie J; Brook, Jenny K (Journal of nursing scholarship, 2014)
PURPOSE: To evaluate a brief educational program about smoking cessation on the frequency of nurses' interventions with smokers, and impact of nurses' smoking status on outcomes. DESIGN: Prospective, single group design with prestudy and 3 months post-study data. METHODS: Nurses in the Czech Republic attended hospital-based 1-hr educational programs about helping smokers quit. They completed surveys about the frequency (i.e., always, usually, sometimes, rarely, never) of their smoking cessation interventions with patients using the five A's framework (i.e., ask, advise, assess, assist, arrange), and their attitudes prior to and 3 months after the course. Demographic data included smoking status. FINDINGS: Among the 98 nurses with prestudy and post-study data, all were female, mean age was 43 years, 33% were current smokers, and 64% worked in a medical or surgical or oncology settings. At 3 months, compared to baseline, significantly (p < .05) more nurses assessed patients' interest in quitting, assisted with quit attempts, and recommended the use of the quitline for cessation. At 3 months after the program, nurses who smoked were less likely to ask about smoking status (odds ratio [OR] = 4.24, 95% confidence interval [CI; 1.71, 10.53]), advise smokers to quit (OR = 3.03, 95% CI [1.24,7.45]), and refer patients to a quitline (OR = 2.92, 95% CI [0.99, 8.63]) compared to nonsmokers, despite no differences in delivery of interventions at baseline. CONCLUSIONS: Three months after attendance at an educational program focused on the nurses' role in supporting smoking cessation efforts, more nurses engaged in interventions to help smokers quit. However, the program was less effective for nurses who smoked. CLINICAL RELEVANCE: This program demonstrated promise in building capacity among Czech nurses to assist with smoking cessation, but nurses' smoking poses a challenge.
Keywords: personál sesterský nemocniční; ošetřovatelství - vzorové postupy; kouření; konziliární vyšetření a konzultace; prevence kouření; Attitude of Health Personnel; ošetřovatelství - výzkum vyhodnocovací; Česká republika; nurses; Smoking Prevention; horké linky; Prospective Studies; Adult; postoj zdravotnického personálu; Czech Republic; Hotlines; Health Care Surveys; Smoking Cessation; Smoking; ženské pohlaví; Humans; prospektivní studie; Practice Patterns, Nurses'; Referral and Consultation; Nursing Evaluation Research; průzkumy zdravotní péče; Nursing Staff, Hospital; dospělí; intervention; Eastern Europe; Female; odvykání kouření; lidé; tobacco